Conflict management approaches under unclear boundaries of the commons: experiences from Danau Sentarum National Park, Indonesia - Yasmi, Yurdi; Colfer, C.J.P.; Yuliani, L.; Indriatmoko, Y.; Heri, V. (2007)
Research on the role of local institutions in confl ict management is still limited. This study highlights various inter-settlement confl icts over the issue of unclear resource boundaries in Danau Sentarum National Park, Indonesia. The park is home to two major ethnic groups (Dayak Iban and Malay) whose livelihoods are highly dependent on fi sh and forest resources available in the park area. We demonstrate how local institutions (adat) are used to address boundary confl icts and consider their effectiveness. The study also discusses challenges that adat face in ensuring the effectiveness of confl ict management. We argue that enhancing communication and developing a mechanism of exchange among settlements engaged in confl ict will promote better understanding of the problem and thus allows improvement in the current approaches in managing confl ict. We propose a co-management arrangement to ensure the sustainability of the park and to constructively manage the confl ict in the area.